Penguatan Kompetensi Komunikasi Anak Melalui Pelatihan Public Speaking Berbasis Edukatif dan Partisipatif di Komunitas Kagem Jogja - Yudaninggar, Kartika Sari; Agusta, Rivga; Muhaimin, Riziq; Gantari, Vania Nidia; Vanya Sandhu, Tabita Atira; Projosusetyo, Bintang Ramadhan (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Public speaking skills are essential in social and academic life but are not yet possessed by many children. This community service program aims to improve children's self-confidence and public speaking skills in the Kagem Jogja Community through training, preparation of learning books, and educational game media. Activities are carried out with a participatory approach through observation, interviews, and direct training. The results of the activities show an increase in children's active participation in public speaking and enthusiasm for fun learning methods. These findings reinforce the importance of early communication education with a contextual and creative approach.